Comparing different sampling methods in order to reconstruct plant economies at the Eneolithic lake dwelling site Stare gmajne, Slovenia - Tjaša Tolar; Anton Velušček (Documenta Praehistorica, 2016)
The results of plant macroremains studies of the Eneolithic (c. 3160–3100 cal BC) lakeshore settlement at Stare gmajne on the Ljubljansko barje in Slovenia are presented. Archaeobotanical material was collected in two different ways: (1) systematic surface sampling from the cultural layer, and (2) judgement sampling from an incompletely burnt large loom-weight. The preservation state and the spectra of plant macroremains were different in both types of samples. The first study primarily deals with the waterlogged plant remains of various types and taxa, while the second deals with carbonised and half-carbonised cereal macroremains, mostly chaff. Both studies confirm the cultivation of main crops: emmer, einkorn and barley.